Advances in Cryogenic Engineering 2000
DOI: 10.1007/978-1-4615-4215-5_7
|View full text |Cite
|
Sign up to set email alerts
|

He II Two Phase Flow in an Inclinable 22 m Long Line

Abstract: In the line of previous work done at CEA Grenoble, large size experiments were performed with the support of CERN for the validation of the LHC two phase superfluid helium cooling scheme. In order to be as close as possible to the real configuration, a straight, inclinable 22 m long line of 40 mm I.D. was built. Very accurate measurements of temperatures and pressures obtained after in situ re-calibration and verified by independent sensors allowed us to validate our two-phase flow model. Although we focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
(5 reference statements)
1
9
1
Order By: Relevance
“…In the framework of LHC cooling scheme studies, we have investigated the thermohydraulic behavior of He II two-phase flow [3,4]. The huge amount of data acquired on previous Cryoloop experiments confirmed the pressure loss predictions given by the Andristos/Hanratty [5] model.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the framework of LHC cooling scheme studies, we have investigated the thermohydraulic behavior of He II two-phase flow [3,4]. The huge amount of data acquired on previous Cryoloop experiments confirmed the pressure loss predictions given by the Andristos/Hanratty [5] model.…”
Section: Introductionmentioning
confidence: 73%
“…Specific devices designed to characterize mist and annular flow were added, whereas heat transfer measurements were maintained and improved. The "Cryoloop II" (figure 1) has already been described previously [4] and mainly consists of an inlet box used to create the inlet quality, a 10 m inclinable straight line of dimensions 42x43 mm, and an outlet saturated bath where excess liquid is evaporated. During a run, total mass flow ( 1 m ) is kept constant using a fixed aperture for the J.…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned and explained [4], wall heat transfer is directly proportional to the inner wetted perimeter of the tube. Heat transfer is improved at high vapour velocities (figure 4).…”
Section: Results and Analysismentioning
confidence: 61%
“…In the same way, from upstream to downstream, we measure the mass flow (Coriolis mass flowmeter), the power used to create the vapor flow, the temperature at both ends of the line and the corresponding differential pressure, the heat transfer through a heat exchange box [2] filled with 1 bar pressurized helium which is converted into an equivalent wetted perimeter (P), and the level of bulk liquid by means of parietal capacitive sensors azimuthally distributed [4]. Two visualization zones are also used to characterize the droplet flow (measurement of interfacial area, velocity and diameter of droplets [5]).…”
Section: Instrumentation Of the Test Linementioning
confidence: 99%
“…The purpose of the Cryoloop experiment [2] was to study the heat transfer capabilities provided by such a flow. We previously showed that, for vapor velocities exceeding typically 4 m/s, the heat transfer between the wall of the pipe and the HeII two-phase flow is improved with respect to a purely stratified situation [3].…”
Section: Introductionmentioning
confidence: 99%